KAJIAN KOMUNIKASI ISLAM YASINAN DAN TABLILAN DALAM PANDANGAN MASYARAKAT - Muhtadin, Muhtadin (Universitas Prof. Dr. Moestopo (Beragama), 2010)
Communication in Islam is a religious proselytizing (da wa) to invite people to believe and practice Islamic faith (aqidah) and law (Shari, a). Yasinan means reciting the verse of Yasin together either in Friday night or certain nights in mosques, praying rooms, or in any hoeses that need it. Tahlil means reciting the verse of